Edukasi Kesehatan Pada Lansia Di Wilayah Kerja Puskesmas Jalan Gedang Rt 06 Rw 02 Kota Bengkulu - Regina Bhayangkara Br. Purba; Ranti Ashabul Jannah; Evita Sari; Putu Indramianti; Vebby Wulan Dica Sari; Delta Aprianti (Jurnal Pakar Pengabdian Kesehatan, 2025)
Hypertension is still a global target for the year 2010 to 2030 (WHO, 2010). High blood pressure is a blood clot in the abdominal arteries that occurs in systolic pressure of more than or equal to 140 mmHg or more than or equal to 90 mmHg (Snyant, 22nd edition of Hypertension. This KKN-T activity is a form of community service aimed at increasing knowledge, awareness and public awareness of the Kelurahan Jalan Gedang about the Risk of Hypertension. Priority activities in accelerating prevention and handling efforts are emphasized in the UPTD program of the Jalan Gedang Health Center. Programs and educational methods, blood pressure checks carried out by Ace Gedang, Gading Cempaka District, Bengkulu City, with the target of 17 Hypertension sufferers and cadres. Information about the causes, signs and symptoms, and the presence of hypertension shows an increase in knowledge. mбутната prevention. This helps people to take better preventive measures and implement preventative measures for treating Hypena.